2008
DOI: 10.1002/ange.200705456
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Metabolically Labeled Glycoconjugates of Living Cells by Copper‐Free and Fast Huisgen Cycloadditions

Abstract: Kupferfreie Klick‐Chemie: 4‐Dibenzocyclooctinol reagiert auch ohne Kupfer(I)‐Katalysator extrem schnell mit azidsubstituierten Sacchariden und Aminosäuren unter Bildung stabiler Triazole. Ein biotinyliertes Derivat eignete sich ideal, um metabolisch mit azidsubstituierten Monosacchariden markierte Glycokonjugate in lebenden Zellen zu verfolgen (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
259
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(274 citation statements)
references
References 28 publications
6
259
0
9
Order By: Relevance
“…However, in this case, only a modest effect was observed (1.5 Â faster than unsubstituted phenyl azide, D), while DIBAC, a dibenzoannulated cyclooctyne, like Sondheimer diyne, showed a large increase in reaction rate (23 Â faster). Puzzled by these contradictory results, a range of substituted aryl azides (F-N) was subsequently synthesized (Supplementary Methods 2) and evaluated in reaction with BCN and DIBAC (entries [6][7][8][9][10][11][12][13][14]. It was found that replacing the o-isopropyl groups with a less sterically hindered but more electronegative halogen group (Cl or F) was favourable for the reaction with BCN, but not for DIBAC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, only a modest effect was observed (1.5 Â faster than unsubstituted phenyl azide, D), while DIBAC, a dibenzoannulated cyclooctyne, like Sondheimer diyne, showed a large increase in reaction rate (23 Â faster). Puzzled by these contradictory results, a range of substituted aryl azides (F-N) was subsequently synthesized (Supplementary Methods 2) and evaluated in reaction with BCN and DIBAC (entries [6][7][8][9][10][11][12][13][14]. It was found that replacing the o-isopropyl groups with a less sterically hindered but more electronegative halogen group (Cl or F) was favourable for the reaction with BCN, but not for DIBAC.…”
Section: Resultsmentioning
confidence: 99%
“…8), or by dibenzoannulation as in dibenzocyclooctyne (DIBO, 2) (ref. 9). Dibenzo-aza-cyclooctyne (DIBAC, 3) first developed by us 10 , also called aza-dibenzocyclooctyne (ADIBO) 11 or dibenzocyclooctyne (DBCO) 12 displayed significantly enhanced reactivity and is currently the most broadly applied cyclooctyne for strainpromoted cycloadditions.…”
mentioning
confidence: 99%
“…Wie Abbildung 2 a zeigt, konnten wir eindeutig eine Population nachweisen, die beide Chromophore, D und A, (S = 0.5, E FRET = 1) enthält. Die hohe FRET-Effizienz dieser Population ist in Einklang mit der Kristallstruktur von GFP, [22] [23] Andere modifizierte Cyclooctine, wie Dibenzocyclooctine, [24] könnten hingegen wegen ihrer Größe die Synthetase und/oder die Translationsmaschinerie des Wirtes vor beträchtliche Herausforderungen stellen. Da pylRS von M. mazei bekanntermaßen auch orthogonal in einer Vielzahl an eukaryotischen Organismen [19,25] …”
Section: Methodsunclassified
“…4a) 67 . To improve the rate, both difluorinated cyclooctynes 92 (DIFO) and dibenzocylooctynes 93 were independently reported allowing the visualisation of dynamic processes. In a particularly striking example, Laughlin et al 94 utilized DIFOs to visualize the development of glycans during zebrafish embryo growth, demonstrating a high degree of specificity and 'bio-orthogonality' at slightly faster rates than previously reported using the Staudinger ligation.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%